Oral inoculation of turkeys with in vitro cultured Histomonas meleagridis in cecal contents results in histomonosis - Catherine Fudge; Olivia Wedegaertner; Katherine Cupo; Justin Lowery; Lin Walker; Frank Edens; Chongxiao Chen (Journal of Applied Poultry Research)
Summary: This study examined the effect of oral administration of Histomonas meleagridis on infection rate and disease progression of histomonosis in turkeys. Experiment 1, poults were placed in 3 experimental groups consisting of H. meleagridis culture in media administered via intracloacal inoculation (CIM), oral inoculation (OIM), or oral inoculation mixed with previously frozen cecal content (OICC). Poults were inoculated with 50,000 histomonads at 8 AM and 5 PM for five days starting from 14-day of age. Cloacal inoculation (CIM) produced 100 % infection rates, while oral infection with H. meleagridis in media (OIM) led to 8 % infection. However, oral inoculations using cecal content (OICC) produced 43 % infection rates (P = 0.0003). In experiment two, poults were placed in 2 experimental groups consisting oral inoculations with fresh cecal contents containing H. meleagridis (OI) and intracloacal inoculations with fresh cecal contents containing H. meleagridis (CI). Poults were inoculated with 50,000 histomonads at 8 AM and 5 PM for five days starting from 14-day of age. Oral inoculations (OI) produced 90 % infection rates, similar to the cloacal route (CI) at 93 % (P = 0.6433). In Experiment 3, individual isolates of H. meleagridis in cecal content were administered orally: Buford isolate (BUF), Arkansas isolate (ARK), or Zeeland, Michigan isolate (ZMI). Results showed BUF and ARK isolates produced higher infection rates than the ZMI isolate (P = 0.0136). In summary, oral infection in turkeys with H. meleagridis could be achieved using cecal content and infection rates and disease progression are impacted by isolate and inoculum condition.